اﻟﺨﻼﻓﺔ اﻻﻣﻮﯾﺔ واﻻﯾﻘﻮﻧﺎت (Journal of the College of Education for Women, 2019)
The analyzation studies for the Umayyad –Bayzantine relationship and attitude of Islamic towards Icons, make us say that there is a relationship between the movement that was against the Icons in Bayzantine Empire and that was in Daral Islam. The declaration of war by the Umayyad Caliphate against the Icons means that the relationship with Byzantine was good. While when the Caliphate became silent means that the relationship with the Bayzantine was bad and distinguished by aggression between the two sides.